SYNTHESIS OF CUMENE (ISOPROPYL BENZENE) FROM ROSIN OIL THROUGH CRACKING AND DEHYDROGENATION - Savitri, -; Nasikin, Mohammad; Rinaldi, Nino; Ramdani, Dadi (LIPI Press, 2013)
Cumene has been synthesized from rosin oil through cracking and dehydrogenation reactions using modified HZSM-5 catalyst. The research has successfully modifi ed the zeolite-based solid acid catalyst by adding Cu-Niand Ni-Mo metal as promoter. Modifi ed HZSM-5 catalysts were characterized using gravimetry and FTIR-pyridine method, and the result showed that the acidity of the catalyst was decreased. Catalyst activity test for cracking anddehydrogenation reactions were carried out to obtain condition of cumene production. The fi nal products were analyzed using GC-MS. Cu-Ni/HZSM-5 catalyst was suitable for the cracking-dehydrogenation reactions of rosinoil to produce cumene with process conditions of 30 bar and 450oC.